Implementation of a Mindfulness Intervention for Women in Treatment for Opioid Use Disorder and Its Effects on Depression Symptoms. (3rd August 2019) - Alexander, Karen; Kronk, Rebecca; Sekula, Kathleen; Short, Vanessa; Abatemarco, Diane
Abstract: Background : Many women in treatment for opioid use disorder (OUD) also experience mental health co-morbidities. Mindfulness intervention has demonstrated effectiveness for improving mental health in the general population, but has not been tested with female populations in OUD treatment. The purpose of this study was to describe characteristics associated with participation in a mindfulness intervention provided to women in treatment for OUD, and also to evaluate the effectiveness of a mindfulness intervention on depression symptoms. Aims : To evaluate participation characteristics associated with a mindfulness intervention and to assess the impact of a mindfulness intervention on depression symptoms for women with OUD. Methods : A secondary data analysis of a mindfulness intervention with women in treatment for OUD was accomplished. Bivariate analysis was conducted to determine any sociodemographic variables associated with intervention participation. Depression scores were assessed pre and post intervention using paired samples t tests for the intervention group ( n = 65) and the control group ( n = 8). Results : A 45% of women in the study reported moderate to severe depression symptoms at baseline, and 63% reported high levels of childhood trauma. There was a significant decrease in depression scores ( M = 3.6 [1.2, 6.1]) following the mindfulness intervention for the intervention group ( t (64) = 3.1, p = .003). Participants entering the intervention group with moderate to severe depression scores experienced the most significant decrease in depression symptoms ( M = 6.6, SD = 13.5), ( t (64) = −2.1, p < .05). Conclusions : Women in treatment for OUD experience high levels of depression symptoms and past trauma, and mindfulness is a feasible intervention for OUD populations which may improve depression symptoms.